TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI RAMBUT SISTEM BORONGAN PADA JASA POTONG RAMBUT - Huda, Muhammad Hasbulloh; Abdul Bais (MAQASHID, 2022)
The practice of buying and selling wholesale systems is one of the buying and selling practices that is commonly carried out by many business actors, one of which is a haircut service business actor. With the many practices of this wholesale system, it is necessary to have a clear review of Islamic law as the basis for the practice of buying and selling. Several opinions from various schools of thought regarding wholesale buying and selling and buying and selling of prohibited materials can become the basis for the practice of buying and selling wholesale carried out by hair cutting services.